Central Europe Towards Sustainable Building (CESB19). (June 2019) - Unknown
Abstract : CESB19 Prague Conference Full Conference Title: Central Europe towards Sustainable Building 2019 Date of the Event: 2–4 July 2019 Location: Prague, the Czech Republic Foreword In October 2015 UN adopted Resolution: Transforming our world: the 2030 Agenda for Sustainable Development. This Agenda is a plan of action for people, planet and prosperity and should stimulate action up to 2030 in areas of critical importance for humanity and the planet. The principal goal is to end poverty, protect the planet and ensure prosperity for all. There are specified 17 Sustainable Development Goals with 169 associated targets which are integrated and indivisible and balance three dimensions of sustainable development: economic, social and environmental. These new goals and targets came into effect on 1 January 2016 and guide the actions up to 2030. It is expected, that all stakeholders, all of us, will work to implement the SDGs Agenda within own countries and at the regional and global levels, considering national specifics and priorities.